Renegotiating Gender and the Symbolic Transformation of Australian Rural Environments - Lockie, Stewart; Lyons, Kristen (The International Journal of Sociology of Agriculture and Food, 2021)
A notable feature of contemporary approaches to ameliorating rural environmental degradation (such as Australia’s National Landcare Program) is the involvement of women to a degree not witnessed in other mainstream farming issues and organisations. At the same time, rural women’s networks are calling for greater recognition of the contribution women make to agriculture and rural communities – to recognise women as ‘farmers’ in their own right – and for a broadening of the agri-political agenda to give greater recognition to non-‘ production’ issues such as social services, workplace health and safety and environmental care. Given the traditional construction of agricultural labour processes in highly masculinised and phallocentric terms, this raises a number of questions regarding the degree to which rural environments are undergoing a sort of symbolic transformation. More specifically, we might question the degree to which these developments provide evidence that human relationships with rural environments – as embodied in the labour process and other day-to-day activities – are being reconceptualised and restructured. To explore this question, we explore data from a variety of sources including ethnographic research conducted with community Landcare groups and organic farmers, and textual analysis of the popular rural press. We conclude that while the renegotiation of gender relations in the labour process is in itself culturally and socially profound, a range of other sociocultural processes may stand in the way of fundamental transformation of the relationships with rural environments implied in those labour processes